Physicochemical properties of carob syrup reveal d-pinitol as an index of sucrose supplementation - Goulas, Vlasios; Aresti, Polina (My University, 2021)
The carob syrup has been attracted the interest of consumers as an alternative sweetener due to its superiority against refined ones. Bioactive phytochemicals and polyols, vitamins and minerals are present in carob syrup; whereas sucrose, fructose and glucose are the main sugars. Although the consumers prefer carob syrup for its special composition, the sucrose supplementation in carob syrup is a common adulteration abating its health benefits. The detection of adulteration in natural sweeteners and honey is usually required time-consuming and advanced analytical techniques. In the present study, the physicochemical properties of carob syrup were studied to pinpoint physicochemical parameters for detection of sucrose supplementation. More specific, moisture, fats, pH, color parameters and total soluble solids were determined. Furthermore, sugar composition of carob syrups was studied using chromatographic separation. Finally, the phenolic fraction and antioxidant activity of carob syrups were estimated. Results showed significant differences in total soluble solids and moisture contents, but these parameters are linked with its preparation procedure. Furthermore, an unexpected fluctuation was observed for D-pinitol and total phenolics contents. Thus, both parameters were determined in genuine and sucrose-supplemented carob syrups. Based on our findings the sucrose supplementation can be detected by D-pinitol content and sucrose to D-pinitol ratio. Therefore, the present work demonstrated the potential of a simple chromatographic separation to detect the adulteration in a traditional Mediterranean product.
Keywords: adulteration; carob syrup; chromatography; D-pinitol; phenolics; sugars